A Pilot Study to Determine the Magnitude of Job Satisfaction among Health Professionals in Riyadh Province - Ahmed, Nehad J. (Asian Journal of Pharmaceutics (AJP), 2022)
Aim: The assessment of job satisfaction may serve as a good indicator of employee effectiveness. This study aimed to describe the magnitude of job satisfaction among health professionals in Riyadh Province. Materials and Methods: The study included health specialists who had diplomas, bachelor’s, master’s, or doctorate degrees in one of the health specialties and worked in public or private hospitals in Riyadh Province. Results: Most of the respondents were females (73.68%) and had a diploma or a bachelor’s degree (92.98%). Moreover, more than 56 % of them had a work experience of at least 6 years. Regarding the overall magnitude of job satisfaction, more than 84% of healthcare workers were satisfied with their work. Conclusion: Health-care organizations should analyze the requested measures to be taken to decrease job dissatisfaction among health-care employees and increase their gratification.